Education and the Decision to Migrate: An Econometric Analysis of Migration in Venezuela - Levy, Mildred B.; Wadycki, Walter J. (Econometrica, 1974)
Interstate labor force migration in Venezuela was estimated for 3 groups of migrants classified by their own educational levels. Regional educational levels and education-specific average wages were included as explanatory variables in order to distinguish between the various effects of education on migration and to estimate differences in the response of educated and uneducated migrants to other explanatory variables. The basic model resembled that used in other econometric studies of migration; migration was assumed to be a function of a number of origin and destination state characteristics which were believed likely to represent costs and benefits of living in various states for most persons. Migration rates rather than absolute numbers were the dependent variable. Zellner's regression technique was employed, and appropriate F statistics were used to test the null hypothesis of equal response of migrants to each of the explanatory variables across educational levels. A substantial proportion of the variance in migration rates was explained for each level of education. The results showed that educated members of the labor force in Venezuela are more mobile and also that there are significant differences in the responses of educated and uneducated migrants to variables which reflect the costs and benefits of alternative locations. The educated were less deterred by increased distance and more responsive to wage rates in alternative locations. The educated appear to be more mobile because of their greater access to information and greater incentives to make additional investments in search of better opportunities. Both educated and uneducated migrants are attracted to more populated regions but the elasticity is almost twice as high for the educated. Educational opportunity was found to be an important locational advantage for those who already had attended secondary school. The less educated are less likely to move to states with high educational levels, perhaps because they fear job competition from the educated. Destination unemployment variables were not highly significant for the uneducated. Results of the study indicate that disaggregation of migration by educational levels is necessary for a clear understanding of the complex relationships involved.